Improved near-surface resolution in geotechnical applications using very early AEM time gates. Issue 1 (2nd January 2020) - Skurdal, Guro Huun; Pfaffhuber, Andreas Aspmo; Davis, Aaron; Bazin, Sara
ABSTRACT: In a majority of geotechnical projects and in geohazard studies, knowledge of sediment thickness is crucial, along with information about sediment types such as possible occurrence of sensitive clay. We test the recently improved system response (SR) method on data from an airborne electromagnetic (AEM) survey carried out in Norway to support ground investigations for linear infrastructure projects. In geotechnical projects, especially the upper metres are important to resolve. The acquisition systems, calibration and data processing and inversion are continuously improved to increase the sensitivity of the AEM systems. SR is applied in the inversion of time-domain AEM data making it possible to utilise the very earliest time gates, which provide information about the shallower layers, aiming to increase the near-surface resolution of the models. We test this new method on data from a site where comparably small resistivity contrasts (5–10 Ωm embedded in 10–50 Ωm) are crucial to resolve, to successfully identify hazardous quick clay. The AEM field data inverted with the full SR provide models with more pronounced structures in the near surface, better reflecting true structures observed in resistivity borehole measurements. We see the same outcome when conducting synthetic modelling. In the synthetic models where these early gates were included, thinner layers with smaller resistivity contrasts are resolved. This is a promising result considering to further use AEM in projects where high resolution in the near surface is essential.